Exploring the notion of Mathematical Literacy teacher knowledge - Bansilal, Sarah (South African Journal of Higher Education, 2018)
The introduction in South Africa of the subject Mathematical Literacy was an innovative response to the low levels of numeracy amongst adults. No other country has developed a subject with such an exclusive focus and this raises challenges for ML teacher educators to design a suitable curriculum to train ML teachers. In this paper I first propose a contextual attributes model of ML. Contextual attributes such as contextual signifiers, language, rules and visual mediators are identified and it is argued that ML learners require opportunities that facilitate engagement with these attributes in order to participate in the domains and make informed decisions. I then explore some implications of this model for the conceptualisation of ML knowledge for teaching.